History of chronic comorbidity and risk of chemotherapy-induced febrile neutropenia in patients with non-Hodgkin lymphoma not receiving granulocyte colony-stimulating factor prophylaxis. Issue 1 (January 2015) - Chao, Chun; Rodriguez, Roberto; Page, John H.; Yang, Su-Jau; Huynh, Julie; Chia, Victoria M.
Abstract We conducted a cohort study to examine the association between a wide variety of chronic comorbidities and risk of febrile neutropenia (FN) in patients with non-Hodgkin lymphoma (NHL) from 2000 to 2009 treated with chemotherapy at Kaiser Permanente Southern California. History of comorbidities and FN events were identified using electronic medical records. Cox model adjusting for propensity score was used to determine the association between a comorbid condition and FN. Models that additionally adjusted for cancer stage, baseline absolute neutrophil count, chemotherapy regimen and dose reduction were also evaluated. A total of 2480 patients with NHL were included, and 60% received CHOP/R-CHOP (cyclophosphamide, doxorubicin, vincristine, prednisone, with or without rituximab). In total, 236 (9.5%) patients developed FN in the first chemotherapy cycle. Anemia (adjusted hazard ratio [HR] = 1.6, 95% confidence interval [1.2–2.2]), HIV infection (HR = 3.8 [2.0–6.7]) and rheumatoid diseases (HR = 2.4 [1.3–4.0]) were associated with significantly increased risk of FN. These results provide evidence that chronic comorbidity increases the risk of FN.